DEVELOPMENT OF AN INSTRUMENT FOR ASSESSING LIBRARY SERVICE QUALITY IN TERMS OF EXCELLENT SERVICE BASED ON SERVQUAL - Widyati, Diana; Sholeh, Muhamad; Karwanto; Roeminingsih, Erny; Amalia, Kaniati (Jurnal Ilmiah Pendidikan Citra Bakti, 2026)
Academic libraries are evolving from traditional repositories into dynamic learning hubs that require continuous evaluation of service quality to ensure excellent service delivery. However, existing measurement instruments such as SERVQUAL and LibQUAL(+) often require contextual adaptation to fully capture user-centered experiences in modern academic libraries. This study aims to develop an instrument for assessing library service quality based on excellent service principles. The study employed a literature-based instrument development approach by reviewing established service quality models and their adaptations in library contexts. The process included identifying key dimensions, constructing indicators, and synthesizing item formulations derived from prior validated frameworks. Emphasis was placed on integrating SERVQUAL dimensions with excellent service indicators relevant to academic library environments. The results indicate that library service quality can be systematically operationalized into several core dimensions, including friendliness, responsiveness, service speed, communication ability, and professionalism. These dimensions are consistently supported by previous empirical studies and can be translated into measurable indicators suitable for Likert-scale assessment. In conclusion, the developed instrument provides a theoretically grounded and contextually relevant framework for evaluating excellent service in academic libraries. It offers a practical basis for future empirical testing and can support library managers in improving service quality based on structured user feedback.